ISOLASI DAN IDENTIFIKASI EUGENOL DARI TANGKAI CENGKEH JENIS ZANZIBAR (Eugenia caryopillata, Thumb) - Fatimah, Feti (Jurnal Entropi, 2007)
A research was done to isolate and identify eugenol from clove stalk of Zanzibar variety. Isolation of clove stalk oil was done using steam destilation technique, and for identification using Gas Chromatography-Mass Spectrophotometer. The isolate from clove stalk oil of Zanzibar variety, fresh and dried variable has 0,565% and 0,485% yield. The oil was yellow and has cloves scent. From the test of clove stalk oil quality, fresh and dried variable was known that its water content were 0,22% and 0,33%., specific weight 1,027 and 1,068 g/mL., with refraction index 1,5186. Beside eugenol, GC-MS analyzes showed that other constituent component in clove stalk oilw were methyl benzena, methyl salisilat, caryophylin oxide, trans-caryophylin, a-Humulene. Eugenol can be isolate from clove stalk oil by the addition of NaOH, acidify with HCl and then extracted using petroleum eter as a solvent. Eugenol that obtained from clove stalk oil, fresh and dried variable were 66,47 % and 76,92%, respectively. Eugenol analysis from isolated clove stalk, fresh and dried variable has 90,10% and 93,96% purities, respectively. Eugenol obtained from fractionation was analyzes using GC, and spiking technique identification.